For Stage II Node-Positive Breast Cancer, is it Worthwhile to Consider Adjuvant Radiotherapy Following Mastectomy? - Osman, Mohammed A. M.; Elkady, Mohammad S.; Nasr, Khalid E. (Frontiers in Oncology, 2014)
Purpose:To evaluate overall survival(OS), progression free survival(PFS), loco-regional recurrence(LRR), and toxicities for early breast cancer patients with 1-3positive axillary lymph nodes, by the addition of radiotherapy to adjuvant chemotherapy. Patients& Methods:Patients were eligible for enrolment into the study if they had pathologically proven stages II breast cancer, with1-3 positive axillary lymph nodes.Patients were assigned to one of the 2groups; Group1;adjuvant chemotherapy then radiotherapy, and group2;adjuvant chemotherapy only. Results:Between September 2008 and August 2014, 75 patients were enrolled. 40 patients group1, and 35 group 2. The 4 year OS for group1, and2 were 77.5%, and 71.4% respectively. The 4 year PFS for group1 and2 were 72.5%, 60% respectively. During the 54 months follow-up period, 11patients from group1 had recurrence (3 locoregional, 7metastatic, and 1both), and 14 patients from group2 had recurrence (7locoregional, 3metastatic, and 4both). The distant metastasis rate was the same in the 2 groups. However, the metastasis sites were different in the 2 groups. Conclusion:The addition of radiotherapy in stage II breast cancer with 1-3 positive lymph nodes improved the PFS, and locoregional recurrence. Radiotherapy improved OS in patients with high risk features.